2019
DOI: 10.1080/19420862.2019.1624464
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the bispecific antibody IgG subclass on T cell redirection

Abstract: T cell redirection mediated by bispecific antibodies (BsAbs) is a promising cancer therapy. Dual antigen binding is necessary for potent T cell redirection and is influenced by the structural characteristics of a BsAb, which are dependent on its IgG subclass. In this study, model BsAbs targeting CD19xCD3 were generated in variants of IgG1, IgG2, and IgG4 carrying Fc mutations that reduce FcγR interaction, and two chimeric IgG subclasses termed IgG1:2 and IgG4:2, in which the IgG1-or IgG4-F(ab) 2 are grafted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…However, in addition to differences in Fc region, variation in the variable region presentation and flexibility of the hinge region affect the functional activity of the IgG class. As reported by Kapelskia et al the hinge region of human IgG subclasses showed different flexibility (IgG1 > IgG4 > IgG2, IgG1 being the most flexible) which significantly influenced the T cell redirection capacity of BsAb (Kapelski et al 2019 ). Furthermore, in another example, eight anti-HER2 biparatopic BsAbs were generated from the same parental mAbs by DVD-Ig platform with different variable domain orientations or linker lengths.…”
Section: Challenges and Considerations For The Development Of Dual Tamentioning
confidence: 91%
See 1 more Smart Citation
“…However, in addition to differences in Fc region, variation in the variable region presentation and flexibility of the hinge region affect the functional activity of the IgG class. As reported by Kapelskia et al the hinge region of human IgG subclasses showed different flexibility (IgG1 > IgG4 > IgG2, IgG1 being the most flexible) which significantly influenced the T cell redirection capacity of BsAb (Kapelski et al 2019 ). Furthermore, in another example, eight anti-HER2 biparatopic BsAbs were generated from the same parental mAbs by DVD-Ig platform with different variable domain orientations or linker lengths.…”
Section: Challenges and Considerations For The Development Of Dual Tamentioning
confidence: 91%
“…Currently, the human IgG1 backbone is commonly used for dual TAAs targeting BsAbs mainly due to its well-known capacity to confer high exposure and long terminal half-life as well as inducing strong secondary immune functions. Many studies have demonstrated that small differences in the amino acid sequence of the CH2 and CH3 domain as well as the glycosylation profile of the Fc domain highly impact antibody thermal stability, pharmacokinetic properties and FcγR-mediated effector functions (Haraya et al 2019 ; Kapelski et al 2019 ; Regula et al 2016 ; Roux et al 1997 ; Zheng et al 2011 ). The human FcγRIII, expressed on macrophages, monocytes, neutrophils, mast cells, and NK cells, binds antibodies with low glycosylation more tightly, thus inducing more potent ADCC effects (Satoh et al 2006 ).…”
Section: Challenges and Considerations For The Development Of Dual Tamentioning
confidence: 99%
“…Because mAbs depend on their Fc region to elicit certain immune reactions, engineering of this domain allows for tactical modification of activity as well as enhancement of the respective physicochemical properties. Sometimes, a simple swap by moving V regions into other IgG subtypes can result in greater efficacy [389,390]. However, there can be a greater emphasis on specific Fc mutagenesis to obtain a more selective IgG effector function [88,355,[391][392][393].…”
Section: Fc Activity Engineeringmentioning
confidence: 99%
“…The role of the anti-CD3-binding domains in BsAb with a broader range of T cell agonism has been shown to have a potential wider therapeutic index [541]. In addition, the choice of the BsAb subtype can affect T cell redirection activity [389]. As the field evolves, more exploration into novel formats with different potency and kinetics of target engagement will expand possibilities for T cell therapeutics [539].…”
Section: Considerations For Selectionmentioning
confidence: 99%
“…Multispecific antibodies that target multiple targets simultaneously have excellent tumour therapeutic potential [38]. By targeting different targets or targeting different epitopes of the same target, multispecific antibody fragments can establish intercellular interactions or synergistic effects to exert significant tumour therapeutic effects [39]. In particular, bispecific antibodies are widely used in tumour immunotherapy and have achieved numerous results.…”
Section: Multivalent Antibody Fragment and Multispecific Antibody Framentioning
confidence: 99%